Legal Implications of Trademark License Revocation on the Trademark Licensee - Assari, Elsa; Murtadho, Achmad; Mufarochah, Sylvia; Putri, Febri Falisa (LEGAL BRIEF, 2025)
The purpose of this research article is to identify and analyze the legal consequences arising from the cancellation of registered trademark rights, as well as to examine the legal protection available to trademark licensees when the original trademark rights have been removed from the General Register of Trademarks. This study employs a normative legal research method, focusing on statutory regulations and judicial decisions. The findings indicate that the cancellation of a registered trademark results in the removal of the trademark from the General Register, the loss of legal protection, legal implications for the licensee, and potential losses for the trademark holder. Legal protection for trademark rights includes sanctions against trademark infringements, which may consist of deletion and cancellation sanctions, compensation, injunctions against further use of the trademark, and additional sanctions, including possible criminal penalties. Liability sanctions are often imposed on trademark registration applicants who have acted in bad faith.